Debt and the effects of fiscal policy - Carlo Favero; Francesco Giavazzi (Federal Reserve Bank of Boston, 2007)
A fiscal shock due to a shift in taxes or in government spending will, at some point in time, constrain the future path of taxes and spending, since the government's intertemporal budget constraint will eventually have to be met. This simple fact is surprisingly overlooked in analyses of the effects of fiscal policy based on vector autoregressive models. We study the effects of fiscal shocks, keeping track of the debt dynamics that arise following a fiscal shock and allowing for the possibility that taxes, spending, and interest rates might respond to the level of the debt as it evolves over time. We show that the absence of a debt feedback effect can result in incorrect estimates of the dynamic effects of fiscal shocks. In particular, omitting an effect of fiscal shocks on long-term interest ratesa frequent finding in studies that omit a debt feedbackcan be explained by the misspecification of these fiscal shocks. Using data for the U.S. economy and two alternative identification assumptions, we reconsider the effects of fiscal policy shocks, correcting for these shortcomings. We close the paper by observing that the methodology described by taking into account the stock-flow relationship between debt and fiscal variables to analyze the impact of fiscal shocks could also be applied to other dynamic models that include similar identities. The inclusion of capital as a slow-moving variable in the study of the relationship between productivity shocks and hours worked is one example.
Keywords: H60; E62; 330; Fiscal policy; VAR models; Finanzpolitik; Schock; Öffentliche Schulden; Steueraufkommen; VAR-Modell; USA